The stimulating effect of extracts of South African plants on melanin production and their antibacterial activity against Cutibacterium acnes - Lall, Namrita (University of Pretoria, 2022)
Dissertation (MSc (Medicinal Plant Sciences))--University of Pretoria, 2022.